It ain't over 'til it's over: The right to strike and the mandate of the ILO Committee of Experts revisited - Claudia Hofmann; Norbert Schuster (International Labour Organization (ILO), 2016)
For many years now, the question of whether the standards of the International Labour Organization (ILO), and the provisions of Convention No. 87 on Freedom of Association and Protection of the Right to Organize (1948) in particular, implied the existence of a right to strike was the subject of a controversy among the tripartite constituents. The debate escalated in 2012, when no agreement was reached at the International Labour Conference of the ILO regarding the adoption and discussion of a list of 25 Member States that stood accused of serious breaches of ILO Conventions. Since then, this issue had continued to hamper the process of supervising the application of ILO Conventions. In 2015, however, the matter seems to have been settled. This working paper reflects on the recent events and decisions by the Governing Body, so as to assess the sustainability of the action taken. It argues that there is still a need for a definite clarification as regards the right to strike and - implicitly also - as regards the mandate of the Committee of Experts.
Keywords: 330; right to strike; ILO Convention; application; supervisory machinery